Harnessing stem cell-derived exosomes: a promising cell-free approach for spinal cord injury - Miaoman Lin; Farzaneh Alimerzaloo; Xingjin Wang; Obada Alhalabi; Sandro M. Krieg; Thomas Skutella; Alexander Younsi (Stem Cell Research & Therapy)
Abstract Spinal cord injury (SCI) is a severe injury to the central nervous system that often results in permanent neurological dysfunction. Current treatments have limited efficacy and face challenges in restoring neurological function after injury. Recently, stem cell-derived exosomes have gained attention as an experimental treatment for SCI due to their unique properties, including superior biocompatibility, minimal immunogenicity and non-tumorigenicity. With their potential as a cell-free therapy, exosomes promote SCI repair by enhancing nerve regeneration, reducing inflammation and stabilizing the blood-spinal cord barrier. This review summarizes advances in stem cell-derived exosome research for SCI over the past years, focusing on their mechanisms and future prospects. Despite their promising therapeutic potential, clinical translation remains challenging due to standardization of exosome isolation protocols, compositional consistency and long-term safety profiles that require further investigation.